Accuracy and precision of the kinetic analysis of counter movement jump performance - Palazzi, D. A.; Williams, B. K.; Bourdon, P. C. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to quantify the accuracy and precision of measuring counter movement jump (CMJ) performance kinetically (i.e. measuring impulse using a force plate). A 14-camera 3D motion analysis system and a force plate were used simultaneously to obtain vertical trajectories of centre of mass (CM) for comparison. Fifty-eight CMJs were analyzed from eleven physically active males. Jump height differences were trivial, and small bias was obtained thereby showing good accuracy as well as small typical errors for performance. Our study indicates that force plates can be used confidently for CMJ analysis.